Peran Forum Pemerhati Galesong dalam Memperkuat Moderasi Beragama di Kabupaten Takalar - Mujizatullah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The focus of this article reveals the Galesong Observer Forum; this forum aims to instill cultural and religious values ​​so that there is harmony and religious adherents to strengthen the harmony and moderation of religious people. This study uses an ethnographic and sociological approach: Data Collection and Analysis Techniques for participatory observation and visual documentation. This article finds that there are efforts to reduce the degeneration of local cultural values. In the traditional bureaucratic order, community leaders are role models, symbols of adat. Thus, all aspects of their life, behavior, and social relations reflect traditional institutions that have the authority to reduce the degeneration of local cultural understanding. In actualizing religious and cultural values ​​to instill values ​​of religious moderation, FPG acts as a forum for the formation of diversity based on religion and belief to increase harmony between religious communities and followers of religions and contribute to strengthening religious harmony and religious moderation.